Desregulação de IL-8 e Claudina-2 no esôfago de pacientes com COVID-19 pós-aguda: implicações para a disfunção da barreira epitelial - Feitosa, Dayllanna Stefanny Lopes Lima (2024)
The COVID-19 pandemic, caused by SARS-CoV-2, has revealed a series of symptoms beyond the respiratory system, including significant gastrointestinal manifestations. Evidence suggests that these symptoms may persist for months after hospital discharge, potentially leading to long-term complications. In this context, the integrity of the esophageal barrier is essential to prevent symptoms such as heartburn and acid reflux. The study aimed to determine the prevalence of esophageal symptoms in post-acute COVID-19 syndrome (PACS) and their possible association with changes in the integrity of the esophageal epithelial barrier. This is a prospective cohort study conducted at a university hospital with individuals hospitalized for COVID-19. Assessments were carried out during hospitalization and between 3 to 6 months after discharge, using questionnaires such as GSRS and RDQ, as well as upper digestive endoscopy with biopsies of the esophageal mucosa. Transepithelial electrical resistance (RET), permeability, and the expression of inflammatory cytokines and junctional proteins were analyzed. The population consisted of 55 individuals, and a significant increase in the intensity and frequency of gastroesophageal symptoms, such as heartburn and reflux, was observed during and after COVID-19. RET and esophageal mucosal permeability were significantly altered in post-COVID patients, with increased levels of IL-8 and Claudin-2. It is concluded that inflammation and esophageal barrier dysfunction are important factors in the perpetuation of post-COVID symptoms.